Novel pathomechanisms of cardiomyocyte dysfunction in a model of heart failure with preserved ejection fraction. (2nd May 2016) - Primessnig, Uwe; Schönleitner, Patrick; Höll, Alexander; Pfeiffer, Susanne; Bracic, Taja; Rau, Thomas; Kapl, Martin; Stojakovic, Tatjana; Glasnov, Toma; Leineweber, Kirsten; Wakula, Paulina; Antoons, Gudrun; et al.
Abstract: Aims: Heart failure with preserved ejection fraction (HFpEF) is increasingly common, but the underlying cellular mechanisms are not well understood. We investigated cardiomyocyte function and the role of SEA0400, an Na + /Ca 2+ exchanger (NCX) inhibitor in a rat model of chronic kidney disease (CKD) with HFpEF. Methods and results: Male Wistar rats were subjected to subtotal nephrectomy (NXT) or sham operation (Sham). After 8 and 24 weeks, in vivo (haemodynamics, echocardiography) and in vitro function (LV cardiomyocyte cell shortening (CS), and Ca 2+ transients (CaT)) were determined without and with SEA0400. In a subgroup of rats, SEA0400 or vehicle was given p.o. (1 mg/kg b.w.) between week 8 and 24. NXT resulted in stable compensated CKD and HFpEF [hypertrophied left ventricle, prolonged LV isovolumetric relaxation constant TAU (IVRc TAU), elevated end diastolic pressure (EDP), increased lung weight (pulmonary congestion), and preserved LV systolic function (EF, dP/dt)]. In NXT cardiomyocytes, the amplitude of CS and CaT were unchanged but relaxation and CaT decay were progressively prolonged at 8 and 24 weeks vs. Sham, individually correlating with diastolic dysfunction in vivo . NCX forward mode activity (caffeine response) was progressively reduced, while NCX protein expression was up‐regulated, suggesting increased NCX reverse mode activity in NXT. SEA0400 acutely improved relaxation in NXT in vivo and in cardiomyocytes and improved cardiac remodelling and diastolic function when given chronically. Conclusions: This model of renal HFpEF is associated with slowed relaxation of LV cardiomyocytes. Treatment with SEA0400 improved cardiomyocyte function, remodelling, and HFpEF.